Evaluasi Struktur dan Skala Upah (SSU) UKM Katering XYZ dengan Metode Skala Ganda Berurutan dan Tumpang Tindih - Utami, Komang Diah Cahya; Prames, Amberly Anadya; Aisah, Prity Nur; Rayyan, Ladwisya Andava; Ningsih, Diana Fitria; Kartika, Lindawati (Ikatan Da'i Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia continue to encounter various challenges such as limited capital, marketing barriers, and management issues, particularly in human resource management. Compensation serves as a crucial factor influencing employee performance and motivation. It is mandatory for every business in Indonesia to formulate a Pay Structure. This research aims to evaluate the Pay Structure of XYZ Catering MSME in Denpasar, Bali based on the 3P principle (Pay for Position, Person, and Performance). The data utilized comprises primary data obtained through in-depth interviews with business managers, supplemented by secondary data sourced from business websites and relevant literature. Job classification is conducted through job value analysis employing pairwise comparison based on 10 compensation factors assessed by business managers. Salary mapping is executed using a simple ranking method with adhered and overlapping double scales. Salary mapping with the adhered method yields a total salary increase of Rp10,218,890 from the initial total salary, whereas overlapping method result in a total salary increase of Rp5,789,746. Based on the analysis, the rectification of pay structure utilizing the overlapping simple ranking method is chosen due to its greater flexibility and offers pay structure improvement that aligns with the company's capabilities.